Translation Technique Of The Book â€œResep Masakan Indonesia Di 5 Benuaâ€ - Pratama, Agus Darma Yoga; Kardana, I Nyoman (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2024)
This research investigates the translation strategies in the bilingual cookbook "Resep Masakan Indonesia di 5 Benua," focusing on Indonesian culinary terms translated into English. The study aims to identify translation techniques, apply Cultural-Specific Items (CSI), and evaluate functional equivalence between Bahasa Indonesia and English. Data were collected from the cookbook using a descriptive qualitative method. The analysis categorized translation techniques based on Newmark's (1998) Molina and Albir's (2002) framework, identified CSIs per Menu, and evaluated functional equivalence using Nida and Taber's theory. Data collection involved reading and categorizing recipes, noting translation techniques, and analyzing CSIs and functional equivalence. Results show Transference as the most dominant technique (53.57%), preserving original Indonesian terms for cultural authenticity. Literal Translation was used in 46.43% of cases for precise translations. Ingredients were the most frequent CSI (82.14%), emphasizing their importance in Indonesian cuisine. Functional equivalence analysis showed a higher use of Formal Equivalence (67.48%) over Dynamic Equivalence (32.52%), indicating a preference for maintaining original structure and terminology. This study highlights the importance of balancing accuracy and cultural adaptation in culinary Translation to maintain recipe authenticity while ensuring comprehensibility. The findings contribute to understanding translation strategies in culinary contexts, emphasizing the challenges and solutions in preserving cultural heritage through language.